SOCIO-PHYSICAL ENVIRONMENTS AND ALGAE/ WATER QUALITY PROPERTIES OF IRRIGATION PONDS: CASE STUDY IN MINAKUCHI AND OTSU, JAPAN - K. Hiramatsu; C. Yanagihara; E. Ichion (Lowland Technology International, 2005)
Irrigation pond called ‘Tameike’ is a type of Japanese traditional rainwater harvesting facilities built to store rain and supply water to farms. It is, however, difficult to sustain a sound management of these systems due to the social changes in Japan, i.e. aging of the rural community and regression of the domestic agricultural industry. Therefore, knowledge, means and ideas are required to maintain irrigation ponds in desirable conditions. In this paper, the water quality, algae and socio-physical environments of 35 ponds in Otsu city and Minakuchi town were investigated and their relations were discussed using the statistical methods; factor analysis and cluster analysis, aiming the acquisition of knowledge for the management. Our investigations revealed that three common factors; ‘scale of the pond’, ‘development of the catchment’, and ‘cultivation in the catchment’ that explain the socio-physical environments. Based on these factors, the ponds were categorized into four types and each compared from the view of trophic levels, diversities and dominant species of algae and location of the pond. It has become apparent that the obtained factors and clusters could explain the tendencies of water quality and diversity, while the relations to dominant species of algae are still ambiguous.